PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 7 PADANG - Adzkia, Fathiya (Jurnal Edukasi dan Penelitian Matematika, 2024)
The first goal of learning mathematics is concept understanding. However, the initial test results indicated that in the number pattern material of class VIII SMP Negeri 7 Padang 2023/2024, students' concept understanding was still relatively low.  The purpose of this research is to find out whether students who use the Discovery Learning model get better results than those who use conventional learning models and to evaluate how students develop during the learning process. This study used quasi-experimental and descriptive research and used a static group design. Class IX of SMP Negeri 7 Padang was the population studied. Quiz and test results showed that the Discovery Learning model was able to improve all indicators observed. Hypothesis testing showed rejection of  due to P-value < α. This result indicates that the application of the Discovery Learning model is more effective than the conventional learning model.Keywords– Discovery Learning, mathematical concept understanding